Towards fluency in Qur’anic reading: a pedagogical analysis of tadarus al-Qur’an practices in madrasah education - Nissa, Khomsatun; Salim, Agus (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
This study examines the relationship between tadarus al-Qur’an practices and students’ Qur’anic reading fluency within the context of Islamic secondary education. Employing a quantitative correlational design, data were collected from 31 students at madrasah through structured questionnaires measuring the intensity of tadarus activities and indicators of reading fluency, including tajwid accuracy, articulation, rhythm, and reading confidence. The data were analyzed using descriptive statistics and simple linear regression. The findings reveal a statistically significant positive relationship between participation in tadarus al-Qur’an and students’ reading fluency (t = 4.225, p < 0.001). The coefficient of determination (R² = 0.357) indicates that tadarus activities account for 35.7% of the variance in reading fluency, suggesting a moderate explanatory contribution. These results indicate that structured and consistent tadarus, supported by active teacher guidance, contributes to the development of students’ fluency in Qur’anic reading, particularly in terms of pronunciation accuracy, application of tajwid rules, and reading confidence. This study lies in specifically conceptualizes Qur’anic reading fluency as a multidimensional construct encompassing phonetic accuracy, rhythmic control, and confidence, rather than treating it as general reading ability. It positions tadarus al-Qur’an not merely as a ritual or habitual activity, but as a structured pedagogical practice grounded in repetition, guidance, and skill internalization. The study provides empirical evidence from the Madrasah Tsanawiyah level, which remains underexplored in previous research, particularly in relation to the integration of habituation-based learning and instructional structuring. However, the findings also suggest that reading fluency is influenced by additional factors beyond tadarus practices, including individual learning motivation and independent reading habits. This study contributes to the discourse on Islamic education by offering a more nuanced understanding of tadarus as a pedagogically meaningful strategy for enhancing Qur’anic literacy. The findings provide empirical and conceptual insights for improving Qur’anic learning practices in madrasah contexts through structured and sustainable approaches.